2013
DOI: 10.1007/s00439-013-1266-7
|View full text |Cite
|
Sign up to set email alerts
|

Imputation across genotyping arrays for genome-wide association studies: assessment of bias and a correction strategy

Abstract: A great promise of publicly sharing genome-wide association data is the potential to create composite sets of controls. However, studies often use different genotyping arrays, and imputation to a common set of SNPs has shown substantial bias: a problem which has no broadly applicable solution. Based on the idea that using differing genotyped SNP sets as inputs creates differential imputation errors and thus bias in the composite set of controls, we examined the degree to which each of the following occurs: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 30 publications
1
49
1
Order By: Relevance
“…41,45,46 In order to increase the sensitivity of our discovery phase, we also considered of potential interest any SNP that did not reach genome-wide significance but were nevertheless associated at P , 10 25 with at least 2 TGP biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,45,46 In order to increase the sensitivity of our discovery phase, we also considered of potential interest any SNP that did not reach genome-wide significance but were nevertheless associated at P , 10 25 with at least 2 TGP biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…40 All SNPs with acceptable imputation quality (r 2 . 0.3) 29,41 and MAF . 0.01 in both imputed GWAS datasets were kept for association analysis.…”
mentioning
confidence: 98%
“…However, both strategies have their weaknesses. The union strategy results in spurious associations in the absence of a genotyping bias and is not a valid approach [1] . The intersection strategy does not introduce spurious associations [1] , but it results in a reduced statistical power due to leaving out some of the available genotyping data.…”
Section: Introductionmentioning
confidence: 99%
“…The correction strategy combines measured genotypes as well as imputed and corrected genotype dosages for SNPs available curacy compared to arrays with sparser coverage. Several studies have shown that imputation errors may bring about biases and spurious associations, and filtering SNPs based on their imputation quality or accuracy before performing association tests cannot eliminate all the false positives [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation